Utilizing Eco-Zno from green synthesis of Musa Acuminata peels and graphene oxide for removal of Cephalexin (CFX) antibiotic in water - Ee, W; Mohamed, RMSR; Al-Gheethi, A; Khamidun, M H; Heshammuddin, NA (2024)
Cephalexin (CFX) antibiotic concentration has been used as a marker for identifying emerging pollutants (EPs) in the non-medical setting due to its significant ability to cause antimicrobial resistance with the highest risk quotient. This study aimed to determine the characteristics of Eco-Zinc Oxide-Graphene Oxide (Eco-ZnO/GO) nanocomposite (NC) from green synthesis of Musa Acuminata by using Field Emission Scanning Electron Microscope (FESEM) coupled with Energy Dispersive X-ray Spectroscopy (EDX). The focus of the study is to optimize the efficiency of Eco-ZnO/GO NC from green synthesis of M. Acuminata for removal of CFX by using adsorption. The Response Surface Methodology (RSM) will be used as well to analyzed the adsorbent dosage, irradiation time, and pH value to obtain the optimum condition of the efficiency of Eco-ZnO/GO for the removal of CFX. The average particle sizes for Eco-ZnO and GO were determined to be 10 nm and 300 nm, respectively, by using FESEM. It is deduced that the optimization factors of adsorbent dosage to 100 mg/L, irradiation time to 120 min, and intial concentration of CFX to 100 mg/L could achieve the mean removal of CFX by 22.17 %. The study contributed to the new knowledge of using nanocomposite materials to remove CFX in the water. However, more thorough studies are needed to obtain higher removal capacity